Soil Moisture Studies in Chir-pine, Teak and Sal Plantations at New Forest, Dehra Dun - Dabral, B. G.; Yadav, J. S. P.; Sharma, D. R. (Indian Forester, 1965)
Soil moisture studies made in the sal, teak and chir-pine plantations indicated that the total soil moisture accretion values for 0-4 feet soil depth were nearly the same for teak and sal, the depletion values being slightly lower under teak than under sal. Chir recorded lower accretion and depletion rates as compared to the other two species. Soil nl0isture accretion and depletion rates varied for each foot depth of the soil mass and showed a close relation between themselves, thereby indicating that the available soil moisture is an important factor in governing the loss of water through evapotranspiration. The actual soil moisture content usually remained below the field capacity. In general, the soils of different species studied showed considerable variations in the moisture content. Apart from the effect of species which was of a lower magnitude under the prevalent climatic conditioJ1s of the locality, the differences in mechanical Composition, water holding capacity and organic matter content of the soil appeared to be of greater importance for these observed variations.